FACTORS INFLUENCING AGROBACTERIUM-MEDIATED TRANSIENT EXPRESSION OF uidA IN CASSIA OCCIDENTALIS LINN EXPLANTS - MUSTRAHALLY RAJAGOPAL; AVULAMANDHA BALAKRISHNA; SADDALA RAJESWARA REDDY; BATHULA SRINIVAS (International Journal of Pharma and Bio Sciences, 2014)
Optimization of co-cultivation parameters during Agrobacterium–mediated transformation to Cassia occidentalis (Linn) evaluated were bacterial density, infection period, wounding and pre-culture of explants, acetosyringone (AS) concentration and co-cultivation temperature. Some of the parameters optimized and resulted in high transformation efficiency were as follows; Agrobacterium tumefaciens growth phase of A600nm 0.17, infection period of 30 min, addition of acetosyringone (AS) in co-cultivation medium (400µM) and in bacterial growth culture. Higher bacterial density resulted in more transformation efficiency, but also higher necrosis in the explants. Dilution of bacterial suspension reduced necrosis in explants and resulted in higher transformation. The transformation efficiency at co-cultivation temperature 25oC was 193 GUS-positive spots per explant and it was increased 6 fold when the infection process was carried out with acetosyringone in co-cultivation medium (400µM) and in bacterial culture (50µM).Our studies proved that among the optimized conditions; the concentration of acetosyringone was the critical parameter during co-cultivation process in Agrobacterium mediated transformation.